University teaching work practices as inclusive social practices - Silva, Joelma Soares; Silva, Francisco Edson Rodrigues da; Pinto, Francisco Roberto (Contextus - Revista Contemporânea de Economia e Gestão, 2024)
Background: Universities must be at the forefront in reducing the effects of social inequalities. In this scenario, professors are decisive actors whose work is the point of connection between a structured social context and the possibility of change. Purpose: Therefore, we aimed to understand how teaching work practices can constitute inclusive social practices. Method: The locus of the research was Universidade da Integração Internacional da Lusofonia Afro-Brasileira (UNILAB). We conducted five semi-structured in-depth interviews with professors who develop extension and research activities related to human diversity in the social conception of the subject. The theoretical-methodological framework was centered on the dialectical-relational perspective of transdisciplinary Critical Discourse Analysis of Chouliaraki and Fairclough (1999). Results: The practices developed by the professors are characterized as inclusive social practices because they intervene and alter the local context permeated by hegemonic ideologies that assert inequalities and cause social change through discourses and events. Conclusions: Teaching is a crucial instrument for challenging prevailing paradigms and fostering diversity in public universities. While such practices can be institutionally aligned with university organizations, they can also become pervasive and transcend institutional boundaries.